Integrating Think Pair Share with Online Collaboration Platforms to Foster Writing Skills - Nisak, Sayida Khiratun; Kuswanto, Kuswanto (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This study examines the implementation of the Think–Pair–Share (TPS) strategy integrated with online collaborative platforms in writing instruction and describes students’ responses and learning experiences related to writing skills. Using a qualitative case study design, the research involved 30 eighth-grade students and an English teacher in a public junior high school in Privat School at Sabak Timur. Data were collected through classroom observations, student and teacher interviews, document analysis of students’ drafts, and records of online collaborative activities. The findings reveal four major outcomes. First, online collaboration strengthened the TPS stages by enabling students to document ideas, revisit discussions, and refine their writing through digital archives. Second, students’ motivation and participation increased due to real-time interaction and peer appreciation. Third, students received more diverse feedback—from partners, groups, and the teacher which improved vocabulary use, coherence, and text length. Fourth, the teacher’s role shifted from a knowledge provider to a facilitator who guided discussions and supported reflective revision. The findings suggest that the use of Think–Pair–Share (TPS) in combination with platforms such as Google Docs facilitated collaborative writing experiences within the studied context, which can be interpreted as aligning with social constructivist principles. The study offers practical implications for English teachers and theoretical contributions to research on digital collaborative writing in secondary education.